EQUILÍBRIO QUÍMICO: ALGUMAS CONSIDERAÇÕES PARTINDO DA ANÁLISE DE LIVROS DIDÁTICOS DE ENSINO MÉDIO E SUPERIOR - Leite, João C. S.; Zambon, Vanessa W.; Mohr, Aline G.; Maldaner, Otavio A.; Zanon, Lenir B. (Salão do Conhecimento, 2013)
Resumo